THE POLICY MODEL FOR SUSTAINABLE COMMUNITY FOREST: A FACTOR ANALYSIS - Sukwika, Tatan; Fransisca, Lidya (Association of Indonesian Forestry and Environment Researchers and Technicians, 2021)
Developing and maintaining forest sustainably is a way to support sustainable development. From the technical point of view, the sustainability of community forest could be articulated not only based on the three aspects i.e. economic (ECO), social culture (SOC), ecology (EGY), but it could also include dimensions of legal and institutional (LIT), as well as accessibility and technology (ACT). This study aims to determine variables of sustainability dimensions that have a direct positive effect on the sustainability of the community forests (SCF), to identify variables that affect SCF and variables of sustainability dimensions that have a major effect on SCF. This study is aiming for 70 samples of forest farmers’ group in Bogor Regency. The respondents were purposively selected based on consideration of the criteria for forest farmer groups namely beginner, intermediate, and advanced. The analysis was conducted based on PSL-SEM tools. Sustainability dimensions of ECO, EGY, LIT, and ACT have a significant positive direct effect on SCF. The mediational hypothesis testing suggested that there is a partial mediation from ECO and EGY to SCF, which is consistent and have a positive value. Based on the coefficient value of the total-effect, among the five dimensions, ecology value was the biggest and the most effect. The policy implies that the ecological aspects considered the importance and strategy. Therefore, the value and productivity of the community forest structure and composition need to be maintained.